EVALUASI KEBIJAKSANAAN PEMBANGUNAN REGIONAL KOTA PADANG PANJANG (PENDEKATAN EXPORT BASE MODEL) - eliza eliza (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2013)
Economic development is an essential factor to development in the country because development was not just about economy fenomena but include material and financial problem in the life many people. So that implementation of suitable policies succeed to achieve many object and purpose of effective development need good planning and evaluation. For example Padang Panjang City, location quotient showed that basic sector is electricity and transportation. base on the result the goverment have to take a policy that actually develop the basic sector until give a big value added to income of the city non basic sector must be develop together with basic sector because connected to economic growth .Keywords : Economic development, location quotient, basic sector electricity